1960
DOI: 10.1172/jci104029
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship of the Normal Bactericidal Activity of Human Serum to Bacterial Infection*

Abstract: The potent heat-labile bactericidal property of fresh mammalian defibrinated blood or serum in vitro has been known since the studies of Nuttall (1) and Buchner (2) over 70 years ago. By 1928, it had been shown that serum components very like those of complement were necessary for this action (3). Although a number of investigators in the fields of bacteriology and immunology have interested themselves in this bactericidal power of fresh serum, little notice has been taken of it in clinical medicine, probably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
1
1

Year Published

1962
1962
1985
1985

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 10 publications
(14 reference statements)
4
98
1
1
Order By: Relevance
“…Serum-resistant strains are encountered, however, and may be frequently isolated from a wide range of infections in man (Roantree & Rantz, 1960;Fierer, Finley & Braude, 1972). Although the mechanism of resistance to the serum bactericidal system has yet to be fully defined, it has been suggested that certain surface structures are able to protect the bacterial cell.…”
Section: Introductionmentioning
confidence: 99%
“…Serum-resistant strains are encountered, however, and may be frequently isolated from a wide range of infections in man (Roantree & Rantz, 1960;Fierer, Finley & Braude, 1972). Although the mechanism of resistance to the serum bactericidal system has yet to be fully defined, it has been suggested that certain surface structures are able to protect the bacterial cell.…”
Section: Introductionmentioning
confidence: 99%
“…The heat-labile opsonins and the bactericidal activity present in normal human sera have both been suggested to be mediated through the recently described alternative pathway of C3 complement activation (17), bypassing the antibody-Cl classical way of activation (8,12). The bactericidal action of normal serum is an important part in host defense (1,2,19,20). Strains of Escherichia coli associated with pathological conditions have been shown to be invariably resistant to the bactericidal effect of serum (16).…”
mentioning
confidence: 99%
“…Five of these 23 sera failed to inhibit the clinical isolate of B. thetaiotaomicron, but all 60 sera inhibited B. vulgatus and B. ovatus at relatively low serum concentrations. Other investigations have also demonstrated bactericidal activity in normal serum against facultative gram-negative pathogens isolated from local infections but not from bacteraemic or septicaemic patients (Roantree and Rantz, 1960;Vosti and Randall, 1970;Young and Armstrong, 1972). The strains of B. thetaiotaomicron, B. vulgatus and B. ovatus that we studied were isolated from localised infections, post-surgical sepsis and an infected malignant ulcer and the B. fragilis was from a blood culture.…”
Section: Discussionmentioning
confidence: 64%